A check-list of Ensifera from Algeria (Insecta: Orthoptera) - Sahnoun, Aouaouche Mohamed; Doumandji, Salah Eddine; Desutter-Grandcolas, Laure (Zootaxa, 2010)
Today Chopard’s 1943, “les Orthoptéroides d’Afrique du Nord", is still the reference book to work on Algerian Ensifera. 49 cricket (Grylloidea) species (16 genera) and 46 katydid and bushcricket (Tettigonioidea, Tettigoniidae) species (21 genera) were then mentioned, in addition to Lezina peyerimhoffi Chopard, 1929 (Stenopelmatidae). Since that time, no recent synthesis has been proposed for Algerian Ensifera, while their taxonomy changed deeply and new species have been described. In the present paper, we propose a reviewed list of Ensifera species from Algeria. All the species mentioned by Chopard (1943) and posterior authors, or collected during our own field work, are mentioned, including new species, i.e. 118 species or subspecies. The geographic localities where these species have been found are given, together with their geographic coordinates, bioclimatic stages and biogeographic zones. These data are used to discuss the diversity and geographic distribution of ensiferan communities in Algeria.